The parameters of a national minimum hourly wage - Philippe Askenazy (Institute for the Study of Labor (IZA), 2014)
Both academic and political debates over the minimum wage generally focus on the minimum wage rate. However, the minimum wage is a complex institution composed of a wide variety of parameters. In this note, I show that nominal rates provide a very crude picture of minimal compensation and of actual employer cost by the comparison of the French, British and US Federal national minimum hourly wages. The extent of their coverage, enforcement procedures, and how the "wage" is defined differ widely between countries. Taking these parameters into account can even alter the comparative hierarchy based on nominal rates alone.
Keywords: J3; J8; 330; minimum wage; exemptions; deductions; international comparisons